Array painting: a method for the rapid analysis of aberrant chromosomes using DNA microarrays. Issue 9 (5th September 2003) - Fiegler, H; Gribble, S M; Burford, D C; Carr, P; Prigmore, E; Porter, K M; Clegg, S; Crolla, J A; Dennis, N R; Jacobs, P; Carter, N P
Abstract : Objective: The authors describe a method, termed array painting, which allows the rapid, high resolution analysis of the content and breakpoints of aberrant chromosomes. Methods: Array painting is similar in concept to reverse chromosome painting and involves the hybridisation of probes generated by PCR of small numbers of flow sorted chromosomes on large insert genomic clone DNA microarrays. Results and Conclusions: By analysing patients with cytogenetically balanced chromosome rearrangements, the authors show the effectiveness of array painting as a method to map breakpoints prior to cloning and sequencing chromosome rearrangements.